Resistance of Vaccinated Mice to Typical and Atypical Strains of Coccidioides immitis - Huppert, M. (1967)
In earlier reports, it was shown that mice and monkeys could be immunized against otherwise lethal challenge doses of Coccidioides immitis arthrospores. The vaccine was composed of Formalin-killed, in vitro grown, endosporulating spherules of C. immitis strain Silveira. In this study, mice were immunized as in the earlier work and then challenged intranasally with arthrospores from seven heterologous strains of C. immitis. Two of these strains were typical of the species, and five were atypical with respect to their cultural characteristics and morphology of microscopic structures. The vaccinated animals were well protected against challenge doses that were lethal to a majority of the control animals, regardless of the strain of fungus employed. The infection ratios among surviving vaccinated and control animals were comparable, but demonstrable lesions were generally smaller and less numerous in the vaccinated groups. It is suggested that these strains are at least immunogenically similar, although not necessarily identical, and that a vaccine prepared from a single strain of C. immitis would be practical for an immunization program.